Research on public logistics centre as tool for cooperation - Jaržemskis, Andrius (Transport, 2007)
This paper focuses on logistics centre concept and benefits for users. Intermodal benefit, forwarders impact, IT solutions, new transport flows due to synergy, better supply chain management, additional services, cost sharing, economies of scale, quality of the services, know‐how, joint marketing impact, and benefit for growth of third‐party logistics services are presented. The main bottlenecks such as duration of planning logistics centres process, pressure to land use for other purposes and problems caused by legislation are described. Results of pilot study of benefits from business cooperation are presented and concluded as well. First Published Online: 27 Oct 2010